Potensi Isolat Jamur Pelapuk Putih Dari Edupark Universitas Muhammadiyah Surakarta Untuk Dekolorisasi Pewarna Red-B - Khotimah, Nurul; , Triastuti Rahayu, S.Si, M.Si (2017)
Decolorization is a way to reduce color density. Biologic decolorization can be done using white rot fungi. Lignolytic enzymes present in white rot fungi are known to degrade dyes. This study aims to determine the potential of white rot fungi of Edupark UMS in decolorizing Batik Red-B dyes. JPP decolorization capability is performed on PDA-C media containing 100 ppm Red-B. JPP is incubated for 14 days. The results show that there are 4 isolates of JPP from Edupark UMS (EP 9, EP 15, EP 21 and EP 23) that can decolorize Red-B dyes. Decolorization can be observed with the appearance of color fading on PDA-C + Red-B media. Keywords: Decolorization, Red-B Dyes, White Rot Fungi